Wavelet-based time-frequency intermuscular beta-band coherence decreases with age but increases after mental fatigue in ankle muscles during gait independent of age - Santos, Paulo Cezar Rocha dos; Barbieri, Fabio Augusto [UNESP]; Lamoth, Claudine; Hortobágyi, Tibor (My University, 2025)
Mental fatigue can affect cognitive function and interfere with motor performance. We examined if mental fatigue affected gait through age-specific modulation of wavelet-based time–frequency intermuscular beta-band coherence in muscles while walking on a treadmill at 1.2 m·s-1. The Psychomotor Vigilance Task, and the AX-Continuous Performance and the Stroop tests were used to induce mental fatigue in groups of healthy young and older participants. Mental fatigue reduced stance time, stride length, and marginally step width and increased cadence, stride length and stance time variability. In older compared with young participants before the induction of mental fatigue, wavelet-based time–frequency intermuscular beta-band coherence measured during walking was lower in the tibialis-peroneus and tibialis-gastrocnemius muscle pairs in specific phases of the gait cycle. In both age groups, after induction of mental fatigue, selected clusters of wavelet-based time–frequency intermuscular beta-band coherence measured during walking increased in the biceps-semitendinosus, rectus-vastus, tibialis-peroneus, gastrocnemius-soleus, and tibialis-gastrocnemius muscle pairs. In conclusion, we observed that while old age might weaken oscillatory coupling between selected ankle muscle pairs during gait, reflecting a certain level of impairment in the descending drive to these muscles, wavelet-based time–frequency intermuscular beta-band coherence measured during gait after mental fatigue migth increase independent of age.
Keywords: Aging; Connectivity; EMG; Gait; Mental fatigability